Potential effects of dams in the geographic range expansion of hylid frogs associated with aquatic macrophytes - Torres, Pablo Javier (2021)
The Fluorescent Frog (Boana punctata) and the Uruguay Harlequin Frog (Lysapsus limellum) are two hylid species found in seasonal swamps and along large rivers in South America. Despite their wide distribution in the Amazon and Paraná River basins, they had never been recorded along the margins of the more than 340 km of the Paraná River in the provinces of Misiones, Itapúa, and Alto Paraná in Argentina and Paraguay. Comparisons of historical and recent satellite images and analyses of the Paraná River structure indicate that the lake formed after the construction of the Yacyretá Dam (140,000-160,000 ha), which has made novel lentic and semi-lentic environments in the tributary streams identified as large inlets, bays, and lagoons. These transformations favored permanent settlement of aquatic macrophytes, mainly Water Hyacinth (Eichhornia crassipes) and floating ferns (Salvinia sp.), which are the characteristic habitat of L. limellum and B. punctata. Because of these changes, we conducted surveys by boat and from shore to determine whether these frog species colonized the novel environments. We found L. limellum and B. punctata at several localities on the margins of Paraná River within the boundaries of the Yacyretá Lake. Because all observations of both species were at sites with abundant macrophytes, and because neither of them were found in field surveys we conducted before 2011 (i.e., when the Yacyretá Lake filled to maximum capacity), our results support the hypothesis that the new records are related to the artificial wetlands created after the construction of the Yacyretá Dam.